Impaired gut junctional complexes feature late-treated individuals with suboptimal CD4+ T-cell recovery upon virologically suppressive combination antiretroviral therapy. (24th April 2016) - Tincati, Camilla; Merlini, Esther; Braidotti, Paola; Ancona, Giuseppe; Savi, Federica; Tosi, Delfina; Borghi, Elisa; Callegari, Maria Luisa; Mangiavillano, Benedetto; Barassi, Alessandra; Bulfamante, Gaetano; d'Arminio Monforte, Antonella; et al.
Abstract : Objective: HIV-infected individuals with incomplete CD4 + T-cell recovery upon combination antiretroviral therapy (cART) display high levels of immune activation and microbial translocation. However, whether a link exists between gut damage and poor immunological reconstitution remains unknown. Design: Cross-sectional study of the gastrointestinal tract in late cART-treated HIV-infected individuals: 15 immunological nonresponders (CD4 + <350 cells/μl and/or delta CD4 + change from baseline <30%); 15 full responders (CD4 + >350 cells/μl and/or delta CD4 + change from baseline >30%). Methods: We assessed gut structure (junctional complex proteins in ileum and colon) and function (small intestine permeability/damage and microbial translocation parameters). The composition of the fecal microbiome and the size of the HIV reservoir in the gut and peripheral blood were investigated as possible mechanisms underlying mucosal impairment. Results: Markers of intestinal permeability, damage, systemic inflammation, and microbial translocation were comparable in all study individuals, yet the expression of junctional complex proteins in gut biopsies was significantly lower in HIV-infected patients with incomplete CD4 + restoration and negatively correlated with markers of CD4 + reconstitution. Electron microscopy revealed dilated intercellular spaces in individuals lacking immunological response to cART, yet not in patients displaying CD4 + T-cell recovery. Analysis of the fecal microbiome revealed an overall outgrowth of Bacteroides–Prevotella spp. with no differences according to CD4 + T-cell reconstitution. Interestingly, HIV reservoirs in peripheral CD4 + T cells and intestinal tissue negatively correlated with immune recovery. Conclusion: These observations establish gut damage and the size of the HIV reservoir as features of deficient immunological response to cART and provide new elements for interventional strategies in this setting. Abstract : Supplemental Digital Content is available in the text